Detection of biomarkers to differentiate endocrine disruption from hepatotoxicity in zebrafish (Danio rerio) using proteomics - Ayobahan, Steve U.; Baumann, Lisa (Chemosphere, 2020)
Measurement of specific biomarkers identified by proteomics provides a potential alternative method for risk assessment, which is required to discriminate between hepatotoxicity and endocrine disruption. In this study, adult zebrafish (Danio rerio) were exposed to the hepatotoxic substance acetaminophen (APAP) for 21 days, in a fish short-term reproduction assay (FSTRA). The molecular changes induced by APAP exposure were studied in liver and gonads by applying a previously developed combined FSTRA and proteomics approach. We observed a significant decrease in egg numbers, an increase in plasma hyaluronic acid, and the presence of single cell necrosis in liver tissue. Furthermore, nine common biomarkers (atp5f1b, etfa, uqcrc2a, cahz, c3a.1, rab11ba, mettl7a, khdrbs1a and si:dkey-108k21.24) for assessing hepatotoxicity were detected in both male and female liver, indicating hepatic damage. In comparison with exposure to fadrozole, an endocrine disrupting chemical (EDC), three potential biomarkers for liver injury, i.e. cahz, c3a.1 and atp5f1b, were differentially expressed. The zebrafish proteome response to fadrozole exposure indicated a significant regulation in estrogen synthesis and perturbed binding of sperm to zona pellucida in the ovary. This study demonstrates that biomarkers identified and quantified by proteomics can serve as additional weight-of-evidence for the discrimination of hepatotoxicity and endocrine disruption, which is necessary for hazard identification in EU legislation and to decide upon the option for risk assessment.
Available online 25 September 2019
Gesehen am 30.01.2020